Profitability as Moderation on The Influence of Green Accounting on Sustainability Development - Pricilia Joice Pesak (Jurnal Riset Akuntansi dan Keuangan, 2024)
Limited natural resources will affect the company's sustainability development. If the government and business people do not manage natural resources properly, it will hamper the sustainability of the Company's development. One way to overcome sustainability development problems is through the application of green accounting. This study aims to examine the influence between green accounting and sustainability development moderated by profitability. Mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period are the population of this study and sampling by purposive sampling so that 102 observational data were obtained. The data was analyzed using the Partial Least Square (PLS) Technique with the help of Smart PLS application version 3.2.9. The results showed that green accounting has no influence on sustainability development and profitability cannot be a moderation variable between green accounting and sustainability development.Keywords. Green accounting; Profitability; and Sustainability Development